Sleep disturbances in HIV infection and their biological basis. (October 2022) - O'Brien, Katie E.; Riddell, Natalie E.; Gómez-Olivé, F. Xavier; Rae, Dale E.; Scheuermaier, Karine; von Schantz, Malcolm
Summary: Antiretroviral therapy has significantly reduced morbidity and mortality in people living with HIV (PLWH). However, a direct consequence of higher survival is the development of ageing-related co-morbidities that have considerable potential to affect quality of life. Sleep disturbances in PLWH are a significant source of morbidity. A meta-analysis has estimated the prevalence of self-reported sleep disturbances in PLWH to be 58%, with commonly identified disturbances including insomnia, obstructive sleep apnoea and poor sleep quality. Not only do sleep disturbances impair daytime functioning, but chronic sleep disruption also associates with metabolic dysregulation and cardiometabolic disease. Therefore, an understanding of the pathogenesis of sleep disturbances in PLWH is important for reducing morbidity and improving quality of life. Several pathophysiological processes in HIV infection may cause sleep-wake dysregulation. In early infection stages, immunological changes such as expression of sleep-promoting cytokines could mediate sleep disturbances. Long term, chronic immune activation, in addition to side effects of antiretroviral therapy, may impact sleep homeostasis more severely, for example through increasing the risk of obstructive sleep apnoea. These sleep disturbances may further contribute to an inflammatory state, due to the bi-directional relationship between sleep and immunity. In summary, further elucidating the link between HIV, immune activation, and sleep is an underexplored avenue for minimising population morbidity and mortality.